Eksplorasi Fenomena Waktu Sebagai Objek Penciptaan Seni Video - Triadiputra, Stephanus Andre (Capture : Jurnal Seni Media Rekam, 2014)
The debate on the speed of time (travel time, the length of the process, working time) has been going on since time immemorial and continues to this day. At this time the meaning of the word quickly in human life not only be the size of an improvement, but it is also considered to be a measure for better circumstances. Around us, the conditions under which it can be said that the central human race by speed. Most of the time of the human life cycle of time spent on a job that runs in a high-tempo pace. Things like that make a man trapped inside a rhythm acceleration. Slow follow the changes are considered outdated. Not fast also believed would make the economic benefits will be slightly reduced. Instead, speed is believed to be able to make financial gains accrue and be used as an indicator of the progress of human life. That is, human life would be considered better if he is able to more quickly than any other human. Through research and phenomenological theory approach the author tries to trace the phenomenon of time. The rhythm of life of modern man feels faster tempo is the main focus. Anxiety that the authors feel the phenomenon push to make it into a work of video art. This video art is a medium of expression that is at once the author tries to explore the phenomenon of modern human life time which more quickly than before. Hopefully, this work could be stand as a contemplation media of the meaning of time for the audience. Keywords: time, fast, phenomenon, phenomenology, and expression